2021
DOI: 10.1016/j.omtn.2021.06.009
|View full text |Cite
|
Sign up to set email alerts
|

Activating the Cpx response induces tolerance to antisense PNA delivered by an arginine-rich peptide in Escherichia coli

Abstract: Cell-penetrating peptides (CPPs) are increasingly used for cellular drug delivery in both pro-and eukaryotic cells, and oligoarginines have attracted special attention. How arginine-rich CPPs translocate across the cell envelope, particularly for prokaryotes, is still unknown. Arginine-rich CPPs efficiently deliver antimicrobial peptide nucleic acid (PNA) to its intracellular mRNA target in bacteria. We show that resistance to PNA conjugated to an arginine-rich CPP in Escherichia coli requires multiple genetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 46 publications
1
25
0
Order By: Relevance
“…2) (Frimodt-Møller et al 2021). In agreement, an activated Cpx-response also conferred a decreased susceptibility to aminoglycosides and another arginine-rich BPP (R 11 ) conjugated to a peptide targeting the DNA sliding clamp (Frimodt-Møller et al 2021).…”
Section: Autonomous Uptake Across the Cytoplasmic Membranementioning
confidence: 62%
See 3 more Smart Citations
“…2) (Frimodt-Møller et al 2021). In agreement, an activated Cpx-response also conferred a decreased susceptibility to aminoglycosides and another arginine-rich BPP (R 11 ) conjugated to a peptide targeting the DNA sliding clamp (Frimodt-Møller et al 2021).…”
Section: Autonomous Uptake Across the Cytoplasmic Membranementioning
confidence: 62%
“…This indicates an indirect autonomous but energy-dependent uptake mechanism, relying on a high membrane potential, for antimicrobials conjugated to such an arginine-rich BPP (Fig. 2) (Frimodt-Møller et al 2021). In agreement, an activated Cpx-response also conferred a decreased susceptibility to aminoglycosides and another arginine-rich BPP (R 11 ) conjugated to a peptide targeting the DNA sliding clamp (Frimodt-Møller et al 2021).…”
Section: Autonomous Uptake Across the Cytoplasmic Membranementioning
confidence: 78%
See 2 more Smart Citations
“…However, other resistance mechanisms not affecting the target, but the import of the peptide and/or degradation of the peptide, could lead to higher tolerance to betatide. It has recently been shown that the activation of the Cpx-envelope stress response system in E. coli can increase the tolerance toward antibacterial peptides and peptide nucleic acids (PNAs) containing arginine-rich CPPs by inhibiting the uptake (Frimodt-Moller et al, 2021). Betatide showed a 2× increase in MIC in Cpx mutant E. coli cells which had a constitutive active Cpx response (Frimodt-Moller et al, 2021).…”
Section: Discussionmentioning
confidence: 99%